DTMB 5415M dynamic manoeuvres with URANS computation using body-force and discretised propeller models. (15th June 2019) - Jin, Yuting; Duffy, Jonathan; Chai, Shuhong; Magee, Allan R.
Abstract: This paper presents model scale computations of self-propelled turning circle and zig-zag manoeuvres for a benchmark combatant DTMB 5415M adopting the unsteady Reynolds-Averaged Navier-Stokes (URANS) equations. A hierarchy of overset grids is utilised to allow rudder deflections while the ship undertakes 6 DOF dynamic motions. With both manoeuvres executed at approach speed corresponds to Fr = 0.41, two different propulsion techniques are applied to drive the free running vessel; the body force propeller model (BFM) and the discretised propeller model (DPM). A verification and validation study is also performed for estimating the numerical uncertainties within the URANS simulated manoeuvres. Comparisons of the results are made between computations adopting the two propulsion approaches and against experimental data from literature. The BFM propulsion method in this study is shown to under-predict the magnitude of propeller induced wake passing the rudders compared to the DPM approach which is able to resolve high fidelity flow physics behind the propellers. In general, the comparison between experimental and numerical results agree mostly within about 10% for the studied turning circle and zig-zag manoeuvres. Highlights: URANS computations on DTMB 5415M turning circle and zig-zag manoeuvres are presented. Ship undertakes 6 DOF dynamic motions using overset grid. Body force propeller and discretised propeller models are applied to drive the dynamic manoeuvres. Results are compared with published experimental data.